Exploration of potential agents for the biological control of the red palm mite, Raoiella indica Hirst (Acari: Tenuipalpidae), on coconut palms in Brazil - Oliveira, Daniel Chiaradia (2015)
The red palm mite, Raoiella indica Hirst (Acari: Tenuipalpidae), has been considered an important pest on coconut palm (Cocos nucifera L.) in the New World. Several studies have been conducted to understand the ecology of this mite, aiming at its control. The search for effective natural enemies to control R. indica has been considered a priority to reduce its importance in areas where it has been newly reported, with special attention to predatory mites of the family Phytoseiidae. Little has been published about the phytoseiid fauna of Thailand, where R. indica has been found at low population levels, perhaps due to the action of natural enemies. The general objective of this thesis was to select promising predatory mites in Thailand (Bangkok and Kamphaeng Saen) to control R. indica on coconut palms in Brazil, to introduce them and to conduct an initial evaluation of their efficiency. Initially, a list of the phytoseiid mites until then reported from Thailand and a taxonomic key to help in their separation were prepared. Thirty two phytoseiid species were known from Thailand before this study; seven new records were presented. The predatory mite fauna associated with R. indica in the central region of Thailand and their population dynamics were assessed. Phytoseiidae was the predatory family most frequently found on coconut and lady palm, Rhapis excelsa (Thunb.) A. Henry, although at low levels (maximum of 0.003 specimens/ cm2 on coconut and 0.008 specimens/ cm2 on lady palm). Amblyseius largoensis (Muma) was the most abundant predator in both sites and on both hosts, except on coconut in Bangkok, which the most abundant was Euseius nicholsi (Ehara & Lee). The levels of R. indica were very low (maximum of 0.03 specimens/ cm2 on coconut and 0.48 specimens/ cm2 on lady palm), compared to what have been reported in other parts of the world. The direct effect of rainfall on the population of R. indica on coconut seedlings in Thailand was evaluated. The results suggested that rainfall reduces considerably the population of R. indica, mainly when the accumulated precipitation in 15 days was over 100 mm. A new mite genus and species of Blattisociidae collected on coconut flowers in Thailand were described. The performances of two predatory mite populations introduced from Thailand, a population previously introduced from La Reunion and a population native from Roraima, Brazil, were compared in relation to their effect on the population of R. indica. The efficiency of the predators could not be demonstrated on coconut seedlings, contrasting with what would be expected from their observed behavior in the laboratory. This result could be due to the overexposure of the predators to sunlight on the leaf surface because of the architecture of the seedlings, probably stimulating them to move to more protected microhabitats. On adult coconut plants, in which the abaxial leaf surface is less exposed, the evaluated predators could have a better performance. Further efforts should be dedicated to evaluate this hypothesis.